Training on Developing CPS Learning Models Using REACT for Science Teachers in Southeast Maluku Regency - Tuhurima, David; Wenno, Izaak Hendrik; Malawau, Seska; Dulhasyim, Ashari Bayu (Pascasarjana Universitas Mataram, 2024)
This community service program (PKM) has the aim of implementing the development of a creative problem solving (CPS) learning model using...Relating, Experiencing, Applying, Cooperating, Transferring(REACT) in science learning that is produced towards aspects of improving student achievement, support for the implementation of junior high school science teacher duties, especially in student-oriented learning design in combining theory and practice, implementing practicums and evaluating science learning outcomes in Southeast Maluku Regency. The expected benefits in this PKM are to motivate teachers to be creative in designing and preparing learning devices in the classroom and laboratory that are oriented towards students based on the environment, so that the learning process can take place properly. While for students, it can provide a clear understanding of the material presented by the teacher, so that students are able to find explanations and provide responses to what they are learning. In addition, students are trained to find out for themselves what they observe and try to describe the concept through student worksheets prepared with the help of the CPS learning model using REACT. Therefore, the CPS learning model using REACT in science learning that is designed is collaborated with several methods, namely reflective lectures, discovery, inquiry, demonstrations and questions and answers and recitations to express various concepts that are being studied in class and can be applied in everyday life